Chimpanzee nesting patterns in savanna habitat: Environmental influences and preferences. Issue 10 (7th May 2013) - Hernandez‐Aguilar, R. Adriana; Moore, Jim; Stanford, Craig B.
Abstract Data on chimpanzee (Pan troglodytes) nesting patterns were collected in Issa, Ugalla, western Tanzania. Ugalla is one of the driest, most open, and seasonal habitats inhabited by chimpanzees. We investigated the physical characteristics of nests and trees used for nesting to understand environmental influences on nest building and identify the characteristics preferred by the chimpanzees and the basis for such preferences. We analyzed 2, 167 nests and 1, 523 nesting trees. Most nests were built in the middle section of the tree crown and close to the tree trunk, and used a single tree in construction. Some physical characteristics of nests (e.g., distance from tree trunk) seemed to be the result of constraints imposed by tree structure. Issa chimpanzees preferred tall trees with high first branches for nesting supporting the hypothesis that elevated height of a sleeping place is a predator defense strategy. The height from the ground to the first branch showed less variation than either tree height or crown height and correlated weakly with tree height, suggesting that height from the ground to the first branch may be a more important factor than tree height alone in selecting a tree in which to nest. As in other study sites, the chimpanzees used tree species in proportions that did not correspond to their abundance suggesting tree species preference. We report for the first time that chimpanzees directionally oriented their nests and propose that this may be to maximize sunlight. We compare our data to those of other chimpanzee study sites. Am. J. Primatol. 75:979–994, 2013. © 2013 Wiley Periodicals, Inc.